2017
DOI: 10.1136/sextrans-2016-052901
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of HIV postexposure prophylaxis (PEP) among highly exposed men who have sex with men (MSM)

Abstract: Twenty-three patients were eligible for the qualitative study. Thirteen interviews were carried out. All patients were 20-60-year-old MSM. The median time between PEP and HIV diagnosis was 3.3 years (interquartile range (IQR)=0.9-4.9). Many participants reported negative PEP experiences: awkward access to the PEP clinic, uneasiness and shame in the hospital setting, unpleasant interaction and moral disapprobation from the medical staff, treatment intolerance and prevention messages that were 'inconsistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…(Cooper) Insofar as the ability to demonstrate a nuanced, open and non-judgmental understanding of the sexual lives of patients is an important factor in HIV healthcare (cf. Palich et al, 2017), there is something of a resonance here with what Maria Puig de la Bellacasa (2017:4) has argued for as 'a politics of care' that, as she puts it, 'engages much more than a moral stance; it involves affective, ethical, and hands-on agencies of practical and material consequence'. Nevertheless, given our interviewees were at the front line of approaching health as a static condition, presumed to be preserved against a pathological viral or bacterial agent (Canguilhem, 1989) or, indeed, a potentially destructive 'chemsex' drug (McCall et al, 2015), much of what we have included here suggests that PrEP not only warrants a reconfiguring of the prevailing conceptions of risk but, more particularly, how it aligns with what can be made possible for the cultures it is intended to serve.…”
Section: Conversations About Sexual Practicementioning
confidence: 95%
“…(Cooper) Insofar as the ability to demonstrate a nuanced, open and non-judgmental understanding of the sexual lives of patients is an important factor in HIV healthcare (cf. Palich et al, 2017), there is something of a resonance here with what Maria Puig de la Bellacasa (2017:4) has argued for as 'a politics of care' that, as she puts it, 'engages much more than a moral stance; it involves affective, ethical, and hands-on agencies of practical and material consequence'. Nevertheless, given our interviewees were at the front line of approaching health as a static condition, presumed to be preserved against a pathological viral or bacterial agent (Canguilhem, 1989) or, indeed, a potentially destructive 'chemsex' drug (McCall et al, 2015), much of what we have included here suggests that PrEP not only warrants a reconfiguring of the prevailing conceptions of risk but, more particularly, how it aligns with what can be made possible for the cultures it is intended to serve.…”
Section: Conversations About Sexual Practicementioning
confidence: 95%
“…Other research topics this month include dual syphilis and HIV screening and diagnostics,7 8 HIV post-exposure prophylaxis for MSM,9 and concordance between partners for Trichomonas vaginalis 10. We also have some thought provoking reflections for our clinical readers about anal cancer in women,11 a challenging perspective on medical communication from a linguist12 and of course our much loved Clinical Round-Up 13…”
mentioning
confidence: 99%
“…Some participants claimed that they were not likely to accept nPEP if adverse drug reactions were intolerable. In previous studies, adverse effects were always one of the important barriers of nPEP implement [27][28][29][30]. But in general, the side effects of ARV medication for most subjects within a short period were relatively moderate, mainly including headache and gastrointestinal symptoms.…”
Section: Resultsmentioning
confidence: 96%
“…HIV and AIDS-related stigma and discrimination were still common in healthcare settings [37][38][39]. A qualitative study in France reported that physicians' aggressive words in face-to-face interactions could bring up negative personal experiences for subjects with ongoing follow-up for HIV infection and PEP history [30].…”
Section: Resultsmentioning
confidence: 99%